ERADICATION OF AL JAMAAH AL ISLAMIYAH IN INDONESIA - Waluyo, Bambang; Jatna, R. Narendra; Wiwoho, Jamal (Yustisia, 2017)
ABSTRACT This article aimed at investigating the implementation of suppression and eradication of terrorism and its organizational existence in Indonesia for the sake of humanity. Apart from the less perfect Law of Terrorism Eradication and no Law specially governing terrorism funding responsively, the law enforcers have successfully used the existing legislations to make Indonesia obey the UN Security Council’s Resolution Number 1267. The verdict against the cases of Zarkasih and Abu Dujana was the first verdict punishing the corporation in Indonesia, by stating that Al Jamaah Al Islamiyah is a forbidden corporation. It also proved the presence of terrorism funding for the first time. In addition, for the first time some assets were taken from Al Jamaah Al Islamiyah through fine of 10 million rupiahs imposed on JI’s administrators, Zarkasih and Abu Dujana respectively. This case handling also proved that law is dependent not only on the legislations but also on the law enforcers themselves